Application of Customer Relationship Management in the Customer Service System of Junaida Furniture Shop Kisaran - Nurdiyanti, Eni; Irianto, Irianto; Dewi, Muthia (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
One industry that is experiencing the impact of these dynamics is the furniture sales industry. Furniture stores, including Junaida Furniture Stores, also face challenges in leveraging technology to improve customer service and optimize their business performance. Even though Junaida Furniture Store has been established since 2021 and offers a variety of household furniture, the ordering process which is still limited to direct visits to the store is an obstacle in increasing sales and retaining loyal customers. In the midst of increasingly fierce competition in the furniture industry, it is important for Junaida Furniture Store to look for solutions that can make it superior and sustainable. Therefore, the proposed solution is to implement Customer Relationship Management (CRM). By utilizing technology to collect and analyze customer data, Junaida Furniture Store can provide more relevant and personalized services. This will increase customer satisfaction and strengthen the bond between store and customer. In the context of increasingly tight business competition, Junaida Furniture Store's competitive advantage will become increasingly visible through quality service and close relationships with customers